Spectrum of HRCT findings in interstitial lung diseases and their correlation with mediastinal lymphadenopathy - Femina, Hussain; Iqbal, Showkathali; Binoj, Varghese; Robert, Ambooken P. (International Journal of Research in Medical Sciences, 2019)
Background: Interstitial lung disease (ILD) represents a heterogeneous non-infectious group of acute and chronic diseases affecting the lung parenchyma. ILDs are usually associated with signiﬁcant morbidity and mortality, particularly when ﬁbrosis occurs. ILD is usually associated with mediastinal lymph node enlargement, the extent of lymph node enlargement may correlate to disease activity or progression of fibrosis. In the present study, authors have correlated the spectrum of high-resolution CT findings in ILDs with mediastinal lymph node enlargements. Methods: One hundred and four cases of ILDs confirmed by HRCT findings and pulmonary function tests were included in this study. HRCT was performed using a GE 128 SLICE CT OPTIMA 660 scanner, USA with 1.5 mm collimation at full inspiration. The findings were classified into three groups-fibrotic, ground glassing and nodular pattern. Authors assessed the presence, number and sites of enlarged lymph nodes (short axis ≥10 mm in diameter). Results: The largest subsets of patients were found in the 51-60 age groups. Fibrotic pattern was the most common pattern in this study (50%) followed by ground glassing (44%). Nodular pattern was the least predominant pattern (6%). Lymphadenopathy was seen in 84% of UIP and 63% cases of NSIP. P value was 0.049 which indicates a significant relation between lymphadenopathy and various ILDs. A strong relationship between lymphadenopathy and the predominant fibrotic pattern followed by ground glassing was observed. Conclusions: A significant association was established between lymphadenopathy and the type of ILD where fibrotic pattern had the maximum association.